Relationship between Knowledge and Attitude of Mothers on Prevention of Dengue Hemorrhagic Fever in Children in the Work Area of the Kawatuna Health Center - Badariati Badariati; Nur Amelia Sino (Journal of Health and Nutrition Research, 2022)
Dengue Hemorrhagic Fever (DHF) is a viral infectious disease transmitted by the Aedes Aegypti mosquito as the main vector and Aedes Albopictus as a potential vector. The knowledge and attitudes of a mother become a benchmark for the mother's awareness of preventing transmission. Efforts to prevent transmission need to be made to reduce the risk of this disease. The purpose of this study was to determine the relationship between knowledge and mothers’ attitudes regarding the prevention of dengue fever in children in the work area of the Kawatuna Health Center 2022. The research method used was quantitative using a cross-sectional approach with a population of 35 mothers with children 6-12 years old and the sample used was 25. respondents. The measuring instrument in this study is a questionnaire and the analysis used in univariate and bivariate analysis. The results showed that the level of knowledge of the respondents in the good category, namely 22 respondents (88%), and for attitudes, namely there were 20 respondents (80%) who had a positive attitude, and there was a significant relationship between the level of knowledge of mothers' attitudes about preventing dengue fever in children. 6-12 years old in the work area of the Kawatuna Health Center with a p-value of 0.001 <0.05. Mothers in the work area of the Kawatuna Health Center are in the independent category, and have a positive attitude, and there is a significant relationship between the level of knowledge and the attitude of mothers toward preventing dengue fever